Discovery of a radiation component from the Vela pulsar reaching 20 teraelectronvolts - Aharonian, Felix A.; Ait Benkhali, Faical; Bernlöhr, Konrad; Ghafourizadeh, Zahra; Hinton, James Anthony; Jankowsky, Felix; Lypova, Iryna; Marx, Ramin; Quirrenbach, Andreas; Rieger, Frank M.; Wagner, Stefan (Nature astronomy, 2023)
Gamma-ray observations have established energetic isolated pulsars as outstanding particle accelerators and antimatter factories. However, many questions are still open regarding the acceleration and radiation processes involved, as well as the locations where they occur. The radiation spectra of all gamma-ray pulsars observed to date show strong cutoffs or a break above energies of a few gigaelectronvolts. Using the High Energy Stereoscopic System’s Cherenkov telescopes, we discovered a radiation component from the Vela pulsar which emerges beyond this generic cutoff and extends up to energies of at least 20 teraelectronvolts. This is an order of magnitude larger than in the case of the Crab pulsar, the only other pulsar detected in the teraelectronvolt energy range. Our results challenge the state-of-the-art models for the high-energy emission of pulsars. Furthermore, they pave the way for investigating other pulsars through their multiteraelectronvolt emission, thereby imposing additional constraints on the acceleration and emission processes in their extreme energy limit.